Structural and thermoelectric behavior of nanostructured porous graphite for thermoelectric power generator application. (2020) - Krishna, Ram; Sreenivasan, M.; Dhass, A.D.; Sivakumar, E.R.; Sai Teja, P.; Dinesh Kumar, M.; Raj Anand, S.
Abstract: Harvesting electrical energy from low-flux sources of waste energy to power portable electronic devices and critical components in remote off-grid areas is to increase the percentage of generation. The sustainable sources, is one of the strategies for minimizing the waste heat. A number of materials for thermoelectric energy generation are being explored and documented. However, carbon-based thermoelectric materials are particularly attractive due to their non-toxic nature, abundance, ease of use and their high specific energy. In this paper, nanostructured porous graphite samples were fabricated from mechanically fragmented graphite flakes to study the structural and thermoelectric behavior. The structural analysis was conducted using Raman spectroscopy, optical and scanning electron microscopy, and thermoelectric characterization was done to at different temperature to measure the Seebeck coefficients/thermoelectric power. The negative and a moderate value of α = −1.5 μVK −1 as compared to other high-cost n-type nanostructured materials used for selection of thermo electric materials.